Burrowing pattern and damage caused by the lesser bandicoot rat, Bandicota bengalensis (Gray) in wheat fields (University Journal of Zoology, Rajshahi University, 2007)
Key words:rat burrow; wheat damage, Bandicota bengalensis Univ. j. zool. Rajshahi Univ. Vol.21, 2002. pp. 5-7